The Effect of Organizational Culture and Altruism on Social Competency of Science Teachers - Desy Angriani (Universitas Riau, 2021)
This study aims to analyze the influence of organizational culture and altruism partially or simultaneously on the sosial competence of science teachers at public Junior high school Dumai. The sample in this study was 71 science teachers at public Junior high school Dumai. The data collection techniques were carried out by distributing questionnaires for the variables of sosial competence, organizational culture and altruism and descriptive analysis and inferential statistics. The results showed that there was a positive and significant influence between organizational culture and altruism on the sosial competence of science teachers 52.10%, meaning that when the organizational culture and altruism were good, the better the sosial competence of the teacher.